2019
DOI: 10.1016/j.cmet.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Released Pyrimidines Inhibit Gemcitabine Therapy in Pancreatic Cancer

Abstract: Highlights d Macrophages polarized by pancreatic cancer cells release pyrimidine nucleosides d Pyrimidine release is a property of alternatively activated macrophage metabolism d Deoxycytidine from macrophages inhibits gemcitabine treatment of cancer cells d Targeting macrophages enhances gemcitabine treatment of pancreatic cancer

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
219
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 328 publications
(243 citation statements)
references
References 43 publications
10
219
0
Order By: Relevance
“…Next, RAW264.7 macrophages co-cultured in 3D with PyVMT breast cancer displayed changes in redox ratio consistent with metabolic changes from tumor stimulation in previous studies ( Fig 4A&C) 90 . Differences in redox ratio and fluorescence lifetime measurements were observed between RAW264.7 macrophages in cytokine-stimulated 2D cultures (Fig 2B-D) and tumor-stimulated 3D cultures ( Fig 4C-E), consistent with reported differences in intracellular metabolite concentration and metabolic flux based on stimulation condition (e.g., cytokines, tumor conditioned media) and culture in 2D vs. 3D 91,92 . Additionally, 3D co-cultured RAW264s exhibited heterogeneous cell-level autofluorescence and pooled gene expression ( Fig 4B, F-H).…”
Section: Discussionsupporting
confidence: 84%
“…Next, RAW264.7 macrophages co-cultured in 3D with PyVMT breast cancer displayed changes in redox ratio consistent with metabolic changes from tumor stimulation in previous studies ( Fig 4A&C) 90 . Differences in redox ratio and fluorescence lifetime measurements were observed between RAW264.7 macrophages in cytokine-stimulated 2D cultures (Fig 2B-D) and tumor-stimulated 3D cultures ( Fig 4C-E), consistent with reported differences in intracellular metabolite concentration and metabolic flux based on stimulation condition (e.g., cytokines, tumor conditioned media) and culture in 2D vs. 3D 91,92 . Additionally, 3D co-cultured RAW264s exhibited heterogeneous cell-level autofluorescence and pooled gene expression ( Fig 4B, F-H).…”
Section: Discussionsupporting
confidence: 84%
“…Certain chemotherapeutic agents, for example doxorubicin, enhance TAM accumulation in the tumour microenvironment, ultimately attenuating their cytotoxic effects . Although the molecular underpinnings are still enigmatic, recent work by Lyssiotis’ group showed that in murine models of pancreatic ductal adenocarcinoma, pyrimidine species released by TAMs inhibit gemcitabine via functional interference with drug uptake and metabolism . This suggests that TAM metabolism is interwoven with that of cancer cells with the potential to modulate the therapeutic response of solid tumours.…”
Section: The Role Of the Innate Immune System In Ccamentioning
confidence: 99%
“…In order to determine differences in the basal metabolic state between PDA and CRC cells, we used LC/MS-based metabolomics [21][22][23][24] to profile a panel of 3 PDA and 3 CRC parental cell lines in exponential growth phase. Analysis of statistically significant differences in the relative abundance of the steady state metabolite pools indicated that the PDA lines had more gluconodelta lactone-6 phosphate (GdL6P) and 6-phospho gluconate (6PG), metabolites in the oxidative arm of the PPP, and smaller metabolite pools of alanine and lactate ( Fig.…”
Section: Differential Metabolic Pathway Activity Between Pda and Crcmentioning
confidence: 99%
“…Thus, we set out to further interrogate the metabolic differences between GOT1 dependent and independent cells, and to determine differential central carbon utilization. To this end we performed isotope tracing metabolomics using either uniformly-labeled 13C (U-13 C) glucose (Glc) or glutamine (Gln) [22][23][24] in the parental PDA and CRC lines. Metabolites were collected from log phase cell lines grown overnight in labeled media, and fractional labeling patterns (Extended Fig.…”
Section: Differential Metabolic Pathway Activity Between Pda and Crcmentioning
confidence: 99%